A new genus and species of primary freshwater crab and a new species of Artopotamon Dai & Chen, 1985 (Crustacea, Brachyura, Potamidae) from western Yunnan, China - Chu, Kelin; Wang, Pengfei; Sun, Hongying (Zootaxa, 2018)
A new genus and species belonging to the primary freshwater crab family Potamidae, and a new species of the genus Artopotamon Dai & Chen, 1985, are described on the basis of remarkable G1and female gonopore characters. Semicirculara lincangensis gen. & sp. nov. and Artopotamon latopeos sp. nov. were collected from southwestern and northwestern Yunnan Province, China, respectively. All type specimens are deposited in Nanjing Normal University in Nanjing and the Institute of Zoology, Chinese Academy of Sciences (IZCAS) in Beijing. Mitochondrial molecular data, from the partial sequence of the mitochondrial 16S rRNA gene, are also shown to support the distinct systematic position of the new taxa.